Centro interactivo con enfoque a la recreación y el deporte (2021)
The project was developed within the department of Tolima and Cundinamarca, specifically in the Girardot-Cajamarca corridor. It is characterized by having a great natural and social diversity, but it presents some social problems, with the master plan it seeks to strengthen the entire area and improve social problems, within the proposed approach, the partial plan in the municipality of Girardot is established the development of a sports-recreational proposal, which benefits native people and tourists. An interactive center with a focus on recreation and sport arises a